Analysis of energetic radiation associated with thunderstorms in the Ebro delta region in Spain. Issue 16 (24th August 2016) - Fabró, Ferran; Montanyà, Joan; Pineda, Nicolau; Argemí, Oriol; van der Velde, Oscar A.; Romero, David; Soula, Serge
Abstract: The analysis of high‐energy background radiation (0.1–2 MeV) enhancements during eight winter thunderstorms and five summer storms in the Ebro delta region in the northeast of Spain is presented. For the first time, high‐energy radiation counts, precipitation, radar reflectivity, and very high frequency lightning detections to infer charge regions altitude have been analyzed in order to find out what produces the measured background radiation increments associated with storms. The good agreement between radar reflectivity and precipitation with increases in background radiation counts coupled with the spectrum analysis comparing rain/no rain periods suggests that radon‐ion daughters play a major role in the radiation increments reported. No evidence has been found supporting that measured background radiation enhancements can be produced by storm electric fields. Finally, a single case of a high‐energy radiation increase was prior to a cloud‐to‐ground lightning stroke, which reinforces the theory that a lower positive charge layer's existence is important for the production of Terrestrial Ground Enhancements. Key Points: Background radiation during thunderstorms Radiation emitted by radon‐ion daughters Experimental evidences of possible TGE detected